2019
DOI: 10.1253/circj.cj-18-0858
|View full text |Cite
|
Sign up to set email alerts
|

Acute Modifications of Left Ventricular Torsional Mechanics Induced by Cardiac Resynchronization Therapy Affect Short-Term Reverse Remodeling

Abstract: Background: Left ventricular (LV) torsion is an important aspect of cardiac mechanics and is altered in heart failure patients. Cardiac resynchronization therapy (CRT) has a positive effect on LV function, but the exact mechanisms through which it works are not completely depicted. Our aim was to investigate (1) the acute CRT effect on LV torsional mechanics in heart failure patients using 3D speckle tracking echocardiography (3DSTE) and (2) its effect on short-term LV remodeling. Methods and Results:We consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…However, it is still uncertain what is the best echocardiographic index of cardiac asynchrony, although recently STE and 3D echocardiography have provided reliable and more predictive data than those used prior to these innovative imaging modalities (16). LV myocardial torsional mechanics are known to be compromised in HF patients (17,18,19), though an increasing interest for its role in assessing improvement to CRT is recently noticed (20). The reasons of this investigating hesitancy might be the low reproducibility of measurements, the complex helical ventricular architecture and contraction and the different vectors' software tools that frequently provide contradictory data of identical phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still uncertain what is the best echocardiographic index of cardiac asynchrony, although recently STE and 3D echocardiography have provided reliable and more predictive data than those used prior to these innovative imaging modalities (16). LV myocardial torsional mechanics are known to be compromised in HF patients (17,18,19), though an increasing interest for its role in assessing improvement to CRT is recently noticed (20). The reasons of this investigating hesitancy might be the low reproducibility of measurements, the complex helical ventricular architecture and contraction and the different vectors' software tools that frequently provide contradictory data of identical phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The LV twist is a sensitive indicator of LV systolic function, which has been established in various populations with multifarious diseases [11][12][13][14] . Heart failure patients scheduled for cardiac resynchronization therapy (CRT) were prospectively studied by Chiara et al [15] . They found that alterations in LV twist take place earlier than variations in LV volumes and LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Особое внимание было уделено методам лучевой диагностики для определения групп пациентов, у которых СРТ будет эффективна [25][26][27]. В ряде работ была показана возможность методов сердечно-сосудистой визуализации выделять пациентов с наибольшей вероятностью обратного ремоделирования ЛЖ через 6 месяцев после СРТ [28][29][30]. В то же время необходимо отметить, что у некоторых пациентов обратное ремоделирование происходит в более поздние сроки [31,32].…”
Section: Introductionunclassified